Gaikwad Snehal Popat - Gaikwad Snehal Popat; Shete Tejashri Balaso; Patil Komal Satish; Prof. Mr.Kumarsagar Dange (Journal of Power Electronics and Devices, 2018)
Even though information devices and systems had been widely applied in steerage provider for museum and exhibitions, there are numerous crucial requirements unhappy. In our studies, we systematically examine the necessities and implementation of system primarily based on ZigBee and ontology. And overcoming the constraints of traditional steering machine quick distance boundaries and network saturation hassle in crowded environments. By implementing this system the person visiting any museum he can guide himself to know the information about the objects placed in museum. Also such system can be implement for another applications also such as in the library for getting the information about books in short time also in CD shop for listening songs.